2021
DOI: 10.1158/2159-8290.cd-20-1202
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive PDACs Show Hypomethylation of Repetitive Elements and the Execution of an Intrinsic IFN Program Linked to a Ductal Cell of Origin

Abstract: 2-1). The collection and processing of the specimens via PancoBank was supported by Heidelberger 48 Stiftung Chirurgie. I.R. is a recipient of an Odysseus I fellowship of the Fund for Scientific Research 49 Flanders (FWO). E.E. was a recipient of an EMBO long-term fellowship (ALTF 344-2013).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 123 publications
7
95
1
Order By: Relevance
“…Because the IFN pathway is involved in anti-viral defense and activated stellate cells are involved in ECM remodeling, this pathway may be activating and reprogramming stellate cells to produce a pro-inflammatory stroma that facilitates tumor growth. Hypermethylation of homeobox genes, which encode key transcription factors of embryonic development, was also commonly detected in several PDA methylome studies [50,58,64,65]. This provides additional evidence that PDA tumors reactivate developmental pathways via epigenetic mechanisms to promote metastatic characteristics.…”
Section: Dna Methylation In Metastasismentioning
confidence: 62%
See 1 more Smart Citation
“…Because the IFN pathway is involved in anti-viral defense and activated stellate cells are involved in ECM remodeling, this pathway may be activating and reprogramming stellate cells to produce a pro-inflammatory stroma that facilitates tumor growth. Hypermethylation of homeobox genes, which encode key transcription factors of embryonic development, was also commonly detected in several PDA methylome studies [50,58,64,65]. This provides additional evidence that PDA tumors reactivate developmental pathways via epigenetic mechanisms to promote metastatic characteristics.…”
Section: Dna Methylation In Metastasismentioning
confidence: 62%
“…Interestingly, Nones et al also observed that stellate cell activation genes were often hypomethylated and therefore, likely downregulated in PDA [63]. In support of this, Espinet et al discovered that stellate cells exposed to conditioned media derived from high-interferon (IFN) signature patient tissues showed an increased stellate cell growth in vitro and tumor formation in vivo [64]. Because the IFN pathway is involved in anti-viral defense and activated stellate cells are involved in ECM remodeling, this pathway may be activating and reprogramming stellate cells to produce a pro-inflammatory stroma that facilitates tumor growth.…”
Section: Dna Methylation In Metastasismentioning
confidence: 93%
“…DNA methylation at CpG dinucleotides is a mechanism of cell-type specific gene regulation inherited in a continuous manner throughout development, hence it is a robust marker of cell identity 50 . Methylation patterns are now considered as a robust method to identify tumor cell-of-origins across tissues 51 , and in different cancer types 47,[52][53][54][55] . In addition, they have been used for characterization of subgroups within a tumor entity, for example in central nervous system tumors 56 , breast cancer 53 , ovarian cancer 57 as well as tissue origin of cell-free DNA (cfDNA) in disease 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Nones et al also observed that stellate cell activation genes were often hypomethylated and therefore, likely downregulated in PDA [20]. In support of this, Espinet et al discovered that stellate cells exposed to conditioned media derived from high-interferon (IFN) signature patient tissues showed an increased stellate cell growth in vitro and tumor formation in vivo [66]. Because the IFN pathway is involved in anti-viral defense and activated stellate cells are involved in ECM remodeling, this pathway may be activating and reprogramming stellate cells to produce a pro-inflammatory stroma that facilitates tumor growth.…”
Section: Dna Methylation and Metastasismentioning
confidence: 93%